SOSIALISASI MANAJEMEN UNTUK MENINGKATKAN PERAN UMKM DALAM PEMULIHAN ECONOMI PASCA COVID 19 DI GAMPONG BEURINGEN KEC. SAMUDERA ACEH UTARA - maryana, maryana; miswar, miswar (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
The implementation of this community service is in the form of outreach and MSME management training. This training was attended by 20 MSMEs in Gampong Beuringen, Samudera District, North Aceh Regency. This training aims to provide understanding to MSME actors about the importance of management knowledge in managing their business. The service method is carried out in several stages, namely the planning stage, the implementation stage and the evaluation stage. The results of this dedication, (1) MSME actors in Gampog Beuringen are able to make venture capital assistance proposals to related agencies and understand the procedures for submitting funding to banks, (2) MSME actors, especially in the field of clothing sewing services, already understand the procedures for developing their products so that they are of interest to customers and (3) MSME actors are proficient in utilizing social media to market their products and services and there are 2 MSME that get business name flyers from the service team. With this activity, MSMEs in Beuringan Gampong can improve the quality and quantity of products/services, high customer demand and income as well as expanding marketing access, so as to improve welfare and have an impact on post-Covid 19 economic recovery.